Influence of seasonality and pollution on the hematological parameters of the estuarine fish Centropomus parallelus - Seriani, Robson [UNESP]; Abessa, Denis Moledo de Souza [UNESP]; Pereira, Camilo D.S.; Kirschbaum, Aline A.; Assunção, Andrea; Ranzani-Paiva, Maria José T. (FapUNIFESP (SciELO), 2013)
This study investigated the hematological parameters of the tropical estuarine fish Centropomus parallelus and their use as a non-destructive biomarker for aquatic pollution. Individuals were collected, in summer and winter, at two estuaries, Cananéia (CAN) and São Vicente (SVE), and blood was extracted by caudal puncture. The evaluated parameters were hematocrit (Ht), red blood cells (RBC), Mean Corpuscular Volume (MCV), and the leukocyte (WBC) and thrombocyte counts. Fishes from CAN showed higher values of absolute number of thrombocytes in the summer. The fishes from SVE presented lower values of Ht and MCV in winter. Comparing the hematological parameters of fishes from these two sites, Ht, MCV, WBC and RBC were higher in fishes from SVE in the summer, whereas during the winter, Ht and thrombocytes were higher in animals from SVE. The results allow attributing the changes in the blood of fishes to seasonality and the presence of contaminants.
Keywords: Centropomus parallelus; Contamination; Estuary; Hematology